A novel gain‐of‐function mutation in ORAI1 causes late‐onset tubular aggregate myopathy and congenital miosis. Issue 5 (23rd November 2016) - Garibaldi, M.; Fattori, F.; Riva, B.; Labasse, C.; Brochier, G.; Ottaviani, P.; Sacconi, S.; Vizzaccaro, E.; Laschena, F.; Romero, N.B.; Genazzani, A.; Bertini, E.; et al.
Abstract : We present three members of an Italian family affected by tubular aggregate myopathy (TAM) and congenital miosis harboring a novel missense mutation in ORAI1 . All patients had a mild, late onset TAM revealed by asymptomatic creatine kinase (CK) elevation and congenital miosis consistent with a Stormorken‐like Syndrome, in the absence of thrombocytopathy. Muscle biopsies showed classical histological findings but ultrastructural analysis revealed atypical tubular aggregates (TAs). The whole body muscle magnetic resonance imaging (MRI) showed a similar pattern of muscle involvement that correlated with clinical severity. The lower limbs were more severely affected than the scapular girdle, and thighs were more affected than legs. Molecular analysis revealed a novel c.290C>G (p.S97C) mutation in ORAI1 in all affected patients. Functional assays in both human embryonic kidney (HEK) cells and myotubes showed an increased rate of Ca 2+ entry due to a constitutive activation of the CRAC channel, consistent with a 'gain‐of‐function' mutation. In conclusion, we describe an Italian family harboring a novel heterozygous c.290C>G (p.S97C) mutation in ORAI1 causing a mild‐ and late‐onset TAM and congenital miosis via constitutive activation of the CRAC channel. Our findings extend the clinical and genetic spectrum of the ORAI1‐related TAM. Abstract :